Simulating a Foreign Policy Dilemma: Considering US Humanitarian Intervention. Issue 3 (19th June 2014) - Switky, Bob
ABSTRACT The humanitarian impulse in the United States routinely clashes with isolationist sentiment, with appeals to the national interest, and with apathy in and out of government. This class exercise encourages students to explore the contours of the debate over humanitarian intervention with a crisis unfolding in Belagua, a fictitious Latin American country. As the crisis deteriorates, students increasingly feel the tension between wanting to help the at-risk civilian population and avoiding a messy conflict from which the United States could have trouble extracting itself. The project requires students to address key questions about the US role in the Belagua case and to consider what the United States could or should have done in actual situations, such as Rwanda and Syria. Because these crises are likely to occur in the decades to come, this exercise initiates students to the challenges that the United States, as well as the international community, undoubtedly will face.